2013
DOI: 10.1071/ah13022
|View full text |Cite
|
Sign up to set email alerts
|

The carbon footprint of an Australian satellite haemodialysis unit

Abstract: State-by-state contributions of energy and water use to the carbon footprint of satellite HD appear to vary significantly. Performing emissions planning and target setting at the state level may be more appropriate in the Australian context. What is known about the topic? Healthcare provision carries a significant environmental footprint. In particular, conventional HD uses substantial amounts of electricity and water. In the UK, provision of HD and peritoneal dialysis was found to have an annual per-patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 9 publications
1
59
0
1
Order By: Relevance
“…The majority of dialysis patients in Australia receive facility based HD, which mandates thrice weekly travel to and from their local healthcare facility. Thus, unsurprisingly travel contributes significantly to the CFP of dialysis in Australia . The survey suggested that few dialysis services are actively attempting to address transport‐related emissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of dialysis patients in Australia receive facility based HD, which mandates thrice weekly travel to and from their local healthcare facility. Thus, unsurprisingly travel contributes significantly to the CFP of dialysis in Australia . The survey suggested that few dialysis services are actively attempting to address transport‐related emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an Australian study from Barwon Health, Victoria, estimated that procurement accounted for 61.6% of the CFP of a satellite dialysis unit, in contrast to 18.6% for electricity usage, 8.8% for patient and staff travel and 7.6% for water usage (see Fig. ) . Meaningful efforts to reduce the dialysis sector CFP must therefore address procurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One Australian study has looked more comprehensively at the combined environmental impact of these and other components of haemodialysis therapy, taking into account the relative contributions of procurement of pharmaceuticals/consumables, medical equipment, energy usage, travel and transport, water usage and waste. The annual per‐patient haemodialysis‐generated carbon footprint was calculated to be 10.2 tonnes CO2‐equivalents, which was more than half the Australian mean annual per capita CO2 emission estimate of 18.8 tonnes CO2‐equivalents …”
Section: How Is This Relevant For Doctors and More Specifically Nepmentioning
confidence: 97%
“…Carbon footprint studies in nephrology are scarce. Only two studies from the United Kingdom and one study from Australia have attempted to calculate the carbon cost of HD, while only one study from China has documented the carbon footprint of PD . Despite this, all are limited in scope and the full carbon impact of dialysis remains a largely unknown quantity.…”
Section: Introductionmentioning
confidence: 99%